External Thermal Insulation Composite Systems: Critical Parameters for Surface Hygrothermal Behaviour - Eva Barreira (2014)
External Thermal Insulation Composite Systems (ETICS) are often used in Europe. Despite its thermal advantages, low cost, and ease of application, this system has serious problems of biological growth causing the cladding defacement. Recent studies pointed that biological growth is due to high values of surface moisture content, which mostly results from the combined effect of exterior surface condensation, wind-driven rain, and drying process. Based on numerical simulation, this paper points the most critical parameters involved in hygrothermal behaviour of ETICS, considering the influence of thermal and hygric properties of the external rendering, the effect of the characteristics of the facade, and the consequences of the exterior and interior climate on exterior surface condensation, wind-driven rain, and drying process. The model used was previously validated by comparison with the results of an "in situ" campaign. The results of the sensitivity analyses show that relative humidity and temperature of the exterior air, atmospheric radiation, and emissivity of the exterior rendering are the parameters that most influence exterior surface condensation. Wind-driven rain depends mostly on horizontal rain, building's height, wind velocity, and orientation. The drying capacity is influenced by short-wave absorbance, incident solar radiation, and orientation.